Consumption and violence : radical protest in Cold-War West Germany - Sedlmaier, Alexander (Ann Arbor : The University of Michigan Press, 2014)
"Combining the tools of political, social, cultural, and intellectual history, Consumption and Violence : Radical Protest in Cold-War West Germany explores strategies of legitimization developed by advocates of militant resistance to certain manifestations of consumer capitalism. The book contributes to a more sober evaluation of West German protest movements, not just terrorism, as it refrains from emotional and moral judgments, but takes the protesters' approaches seriously, which, regarding consumer society, had a rational core. Political violence is not presented as the result of individual shortcomings, but emerges in relation to major societal changes, i.e., the unprecedented growth of consumption. This new perspective sheds important light on violence and radical protest in post-war Germany, as previous books have failed to examine to what extent these forms of resistance should be regarded as reactions to changing regimes of provision. Continuing the recently growing interest in the interdependence of countercultures and consumer society, the focus on violence gives the argument a unique twist, making the book thought-provoking and engaging"--
Department Stores : Political Protest in the Commercial Sphere -- Neo-Marxist Critiques of Affluent Society : "Need to Break the Rules" -- Consumer Society under Fire : The Militant Targeting of an Abstract Enemy -- Public Transport : Protest against Fare Increases -- The Media : The Anti-Springer Campaign -- Urban Space : The Squatting Movement -- Global Responsibilities : In Search of Consumer Morality and Solidarity.
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2016. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Political violence -- Germany (West) -- History; Protest movements -- Germany (West) -- History; Radicalism -- Germany (West) -- History; Government, Resistance to -- Germany (West) -- History; Consumption (Economics) -- Political aspects -- Germany (West) -- History; Capitalism -- Political aspects -- Germany (West) -- History; Social change -- Germany (West) -- History; Germany (West) -- Politics and government; Germany (West) -- Social conditions; Germany (West) -- Economic conditions; Electronic books